James 'Happ' & Marian Edwards 50th anniversary (Raton Range Raton, New Mexico, 1991)
Newspaper Article on the 50th Anniversary of James and Marian Edwards.
Master list item #: 61
File location is in the Raton File Cabinet
Keywords: Edwards, James; Edward, Marian; Sprague, Dorothy; Rambo, Ann; Miller, David; Miller, (Mrs.); Buxton, Janis; Humphries, Edwin; Edwin, Mary Jo; Van Zant, Joel; Van Zant, Gretchen; Thaxton, Grace; Mangino, Glenna; Briscoe, Alta; Dornacker, John; Schlegel, Karen; Schlegel, Paul; Phillips, Elliott; Phillips, Virginia; Robinson, Carol; Davis, Les; Davis, Linda; Davis, Warren; Davis, (Mrs.); Davis, Randy; Davis, (Mrs.); Davis, Kirk; Davis, (Mrs.); Davis, Bruce; Davis, (Mrs.); Barmann, Eric; Barmann, Kim; Porter, Jiggs; Raton Country Club; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Greencastle, Indiana; La Junta, Colorado; Seminole, Texas; Santa Fe, New Mexico; Marina del Rey, California; Albuquerque, New Mexico; Miami, ?; Bloomington, Indiana; Cimarron, New Mexico